Neutron scattering - magnetic and quantum phenomena - Fernandez-Alonso, Felix; Price, David L. 1940- (Academic Press, 2015)
Neutron Scattering - Magnetic and Quantum Phenomena provides detailed coverage of the application of neutron scattering in condensed matter research. The book's primary aim is to enable researchers in a particular area to identify the aspects of their work where neutron scattering techniques might contribute, conceive the important experiments to be done, assess what is required to carry them out, write a successful proposal for one of the major user facilities, and perform the experiments under the guidance of the appropriate instrument scientist. An earlier series edited by Kurt Sköld and David L. Price, and published in the 1980s by Academic Press as three volumes in the series Methods of Experimental Physics, was very successful and remained the standard reference in the field for several years. This present work has similar goals, taking into account the advances in experimental techniques over the past quarter-century, for example, neutron reflectivity and spin-echo spectroscopy, and techniques for probing the dynamics of complex materials of technological relevance. This volume complements Price and Fernandez-Alonso (Eds.), Neutron Scattering - Fundamentals published in November 2013.
Keywords: Neutronenstreuung